Food ordering mobile application for cafeterias in campus / Syamimi Zakaria - Zakaria, Syamimi (2022)
The development is now accelerating especially when it involves technology. Such development became more aggressive when the world was hit by a pandemic. The online Food Ordering Mobile Application for Cafeterias in Campus is proposed to simplify the existing food ordering process. The proposed system is provided the users an interfaces as well as menu options that can facilitate both the administrator and students. The system designed for both administrator and students that enable them to get the notification from students’ orders so that they will not missing it. Other than that, students can choose more than one item to make an order also can view order details while for administrator they can manage order from student also can update new menus at their café. Other features in this food ordering mobile application for cafeterias in campus are, both user which administrator and students can communicate each other in chats page. In developing the mobile application, a suitable development methodology has been implemented using Waterfall Model as guideline. The Waterfall Model has different phases in development such as analysis, design, implementation, testing, deployment, and review. The food ordering mobile application for cafeterias in campus has been designed using three principles which are navigation intuitive, legible text content and hand position controls it has been developed using Android Studio with Firebase as a database. It was evaluated by distributing questionnaires to 30 respondents which contained questions from usability testing. Functionally test was conducted using test script. The test result revealed that the mobile application platform is suitable to use but needs to be refined and improved.